Young Entrepreneurship in the Digital Age: Young People's Entrepreneurial Journeys through Social Media: Young Entrepreneurship in the Digital Age - Uygur, Sebahat Sevgi (Studia Psychologica, 2026)
This study examines how young entrepreneurs utilize social media platforms in their entrepreneurial processes, focusing on the opportunities and challenges these platforms present and the psychological mechanisms that influence their experiences. Using Q methodology, the study explores young entrepreneurs’ self-expression, idea and skill development, feedback reception, and the impact of social media’s competitive environment. The research sample consists of 20 Turkish young entrepreneurs (aged 18–34) who actively engage in entrepreneurial activities through social media. The Q method analysis findings highlight three key factors shaping entrepreneurs’ perceptions: Opportunities of Social Media, Psychological Impacts of Rivalry and Feedback, and Critical Perspective. Social media was viewed as a double-edged sword, simultaneously enabling creativity and networking while presenting challenges such as trust and psychological pressures. Gender-based differences emerged, with women emphasizing collaboration and opportunity while men focused on competition and feedback. Furthermore, the content analysis findings revealed both positive and negative perceptions, underscoring the dual role of social media as a driver of innovation and a source of stress. This study contributes to the growing literature on social media and entrepreneurship by offering a culturally contextualized understanding of how Turkish young entrepreneurs navigate the opportunities and challenges of digital platforms.